Bättre med byxor eller Vad gör alla dessa kvinnor på scenen? - Rosenberg , Tiina (Tidskrift för genusvetenskap, 1997)
This a r t i d e discusses the the seductive element of looking at females in breeches (female parts where women dress like men) through the eyes of queer theory, but also highlights the risks with such an undertaking. The a r t i d e also discussed the subversive n a t u r e of women in drag in productions of m o d e r n opera, an area where this aspect is sadly u n d e r r a t e d . Rosenberg gives a few examples f r om her research around drag and relätes this to Rudolf Dekkers’ and Lotte van der Pol’s survey Kvinnor i manskläder: En avvikande tradition; Europa 1500-1800 /Women in drag. A divergent tradition; Europé 1500-1990/.